A framework for fast automatic image cropping based on deep saliency map detection and gaussian filter. Issue 3 (4th May 2019) - Rahman, Ziaur; Pu, Yi-Fei; Aamir, Muhammad; Ullah, Farhan
ABSTRACT: Extracting robust visual saliency map and image cropping are fundamental problems in computer vision, graphics, and so on. It is not easy task to accurately detect and crop the entire salient object from images with complex background. In this paper, a deep learning strategy is adopted to train a large data-set of images, to get saliency map from the input image using graph-based segmentation and gray level adjustment to enhance and extract more accurate and clear saliency map. Furthermore, the Gaussian filter and image scaling used along with cropping method to keep better presentation of the visual object. The important task of overall framework is to take care about relevant image contents as well as to identify more region of interest and get optimum rectangle from the saliency map with minimum and maximum rectangular windows. Quality and low computational complexity have been focused while performing the cropping operation because automatic and efficient cropping technique should not only rely on geometric constraints, but it should be fast enough to consider the important image contents. The applied method use different data-set of images, to ensure the efficiency of this technique and the experimental results show that the framework is not only fast as well as much better for image cropping. We used Matlab and Caffe framework for efficient experimental results.